ABC APPLICATION USER SATISFACTION ANALYSIS WITH APPROACH END USER COMPUTING SATISFACTION (EUCS) - Hasna Khansa Aulia; Eka Murtiasri; Budhi Adhiani Christina (Politeknik Negeri Semarang, 2022)
This study aims to examine the effect of ABC application user satisfaction levels using the End User Computing Satisfaction method. The independent variables in this study are content, accuracy, format, ease of use, timeliness, while the dependent variable is user satisfaction. This research is a quantitative study using primary data and secondary data. The population in this study were all ABC application user with sample amounted to 100 respondents. Collecting data through the distribution of online questionnaires with a google form. The method of analysis used in testing the hypothesis is multiple linear regression analysis. The results showed that the variables of content, accuracy, format, ease of use, timeliness partially had a significant positive effect on user satisfaction of the ABC application, and simultaneously variable content.